2016
DOI: 10.1080/14729679.2016.1140587
|View full text |Cite
|
Sign up to set email alerts
|

Why do children not play in nearby nature? Results from a Norwegian survey

Abstract: Based on a nationwide Norwegian survey among 3160 parents of children aged 6-12 years, this article identifies and discusses barriers for children's engagement with nearby nature. A set of social factors related to time pressure are evaluated as more significant barriers than environmental factors such as accessibility, safety and landscape quality. Children's free play in nearby nature does not seem to be an alternative to a target-orientated and time-scheduled everyday life. Instead, parents give themselves,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 38 publications
6
55
0
2
Order By: Relevance
“…It was not possible in this study to discern the reasons why respondent parents’ children do not regularly participate in risky play. However, comments from North American [30] and Norwegian [73] parents discussing outdoor free play highlight busier school schedules (e.g., homework, music, organised sport) and increased use of technology as barriers to unstructured play. Notably, these activities were not necessarily viewed as detracting from children’s development, rather the skills gained thought of as essential for the future and preventative of troublesome behaviour [30], a sentiment also captured by a New Zealand study [28].…”
Section: Discussionmentioning
confidence: 99%
“…It was not possible in this study to discern the reasons why respondent parents’ children do not regularly participate in risky play. However, comments from North American [30] and Norwegian [73] parents discussing outdoor free play highlight busier school schedules (e.g., homework, music, organised sport) and increased use of technology as barriers to unstructured play. Notably, these activities were not necessarily viewed as detracting from children’s development, rather the skills gained thought of as essential for the future and preventative of troublesome behaviour [30], a sentiment also captured by a New Zealand study [28].…”
Section: Discussionmentioning
confidence: 99%
“…A narrow path will keep the visitor closer to the forest environment and nature, and enhance a more bodily nature experience including exercises like jump, bend down, climb, etc. [9,45,46]. This is especially important for children, and a path can provide more unstructured environments and opportunities for discovery and play for children [47].…”
Section: Preferences For Forest Infrastructurementioning
confidence: 99%
“…Our findings in this study indicate that many of the teachers have observed some cultural changes among their pupils, including a decline in their physical skills and amount of friluftsliv experience compared to former pupils. A decline in youth outdoor skills and experiences seems to be a general trend, locally and globally (Clements, 2004;Karsten, 2005;Skaar et al, 2016). Furthermore, the findings show that many teachers are changing their own focus and attitudes on safety as compared to former excursions, with the teachers saying they are now taking more precautions in regard to the length, duration and location of excursions.…”
Section: Discussionmentioning
confidence: 86%